2017
DOI: 10.1371/journal.pone.0169846
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Plasmid Copy Number with Single Colour Droplet Digital PCR

Abstract: Bacteria can be considered as biological nanofactories that manufacture a cornucopia of bioproducts most notably recombinant proteins. As such, they must perfectly match with appropriate plasmid vectors to ensure successful overexpression of target genes. Among many parameters that correlate positively with protein productivity plasmid copy number plays pivotal role. Therefore, development of new and more accurate methods to assess this critical parameter will result in optimization of expression of plasmid-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…(pBR322 ori; ϳ20 copies per cell [27]) in the ΔflaA-E strain in the presence of 0.2% arabinose. Motility increased with increasing copy number of flaA expressed from flaAp, demonstrating that relatively large amounts of FlaA are necessary for monoflagellin filament formation.…”
Section: Resultsmentioning
confidence: 99%
“…(pBR322 ori; ϳ20 copies per cell [27]) in the ΔflaA-E strain in the presence of 0.2% arabinose. Motility increased with increasing copy number of flaA expressed from flaAp, demonstrating that relatively large amounts of FlaA are necessary for monoflagellin filament formation.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in plasmid copy number between Oltmanns et al [ 21 ] and this study may result from the assay method, Agrobacterium strain, or growth time difference. Plasmid copy numbers are determined primarily by their replication origins, which show significant cell-to-cell variation within every population [ 32 ]. Oltmanns et al [ 21 ] reported 15–20 copies/cell with pTF::Ri carrying RepB Y299H and repB T486C mutations in A .…”
Section: Resultsmentioning
confidence: 99%
“…The difference in plasmid copy number between Oltmanns et al [14] and this study may result from the assay method, Agrobacterium strain, or growth time difference. Plasmid copy numbers are determined primarily by their replication origins, which show significant cell-to-cell variation within every population [28]. Oltmanns et al [14] reported 15-20 copies/cell with pTF::Ri carrying RepB Y299H and repB T486C mutations in A. tumefaciens EHA105 using a DNA blot assay, whereas in this study we estimated that both the single and the double mutations in a nopaline-type ABI strain have 9-10 copies/cell, using a ddPCR assay.…”
Section: Resultsmentioning
confidence: 99%